Revolution or Disruption? Implications of Precision Livestock Farming (PLF) for Traditional Livestock Systems in Indonesia - Firhamsah, Ikhwan; Gifari, Zaid Al; Nurjannah, Luluk Lailatun; Pertiwi, Eva Amalia; Wandira, Ica Ayu (Universitas Bengkulu, 2025)
Precision Livestock Farming (PLF) is a modern approach to livestock management that leverages sensors, the Internet of Things (IoT), and artificial intelligence to enhance efficiency, productivity, and animal welfare. In developed countries, PLF is regarded as a revolution in the livestock sector; however, in the context of traditional livestock farming in Indonesia, particularly among small-scale beef cattle farmers, its implementation poses a dilemma between opportunities for transformation and risks of disruption. This systematic review, conducted in accordance with the PRISMA framework, critically examines the implications of PLF for traditional farmers by synthesizing literature from Scopus, Web of Science, ScienceDirect, and Google Scholar (2010-2024). Through thematic analysis of 40 selected studies, we find that PLF offers substantial benefits, including improved feed efficiency, early disease detection, and enhanced animal welfare, but also faces significant barriers, such as high investment costs, limited infrastructure, low digital literacy, and risks of smallholder marginalization. By integrating evidence from both technological and socio-economic perspectives, this review provides a holistic analysis of PLF’s dual role as both a transformative tool and a potential disruptor in developing agricultural contexts. The findings underscore the necessity of context-sensitive adoption strategies, informed by incremental technology introduction, supportive policies, targeted subsidies, cooperative models, and capacity-building initiatives. This study contributes to the literature by offering a policy-relevant framework for aligning PLF with inclusive and sustainable livestock development in Indonesia and similar settings.